Clay Raw Material of Medieval Pontic Amphorae (to the Question about Production Areas) - Evgeniy V. Sukhanov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. Amphorae is a significant part of pottery from the early medieval sites of Pontic region. They are traditionally considered as important source for analyzing the chronology, directions and intensity of ancient trade links. The paper is devoted to comparative analysis of clay raw material used for making medieval pontic amphorae. These ceramic containers are wide spread in the sites of the 8th - 10th centuries in Crimea, Taman, the Don and the Volga river basins and in other areas.